PENGARUH KURS YEN, HARGA ACUAN BATU BARA, HARGA LNG DAN PRODUKSI BATU BARA TERHADAP EKSPOR BATU BARA INDONESIA KE JEPANG - Adhy Satya Pratama; Witri Yuliawati; Djuanda Hatta; Shalahuddin Shalahuddin (Universitas Ichsan Sidenreng Rappang, 2025)
This study examines the influence of yen exchange rate, coal reference price, LNG price, and coal production on Indonesian coal exports to Japan to understand bilateral energy trade dynamics in optimizing Indonesian coal exports. This quantitative explanatory research uses time series data from 2000-2023. The study aims to comprehensively analyze the influence of economic variables on coal exports. The research results show that only the LNG price variable has a significant positive effect with a coefficient of 0.2311, while yen exchange rate, coal reference price, and coal production have no significant effect, which becomes the main finding from this multiple regression analysis. Additionally, the ability of the four variables to explain 69.41% of coal export variation indicates a good model in explaining the energy substitution phenomenon. Therefore, export strategies that consider LNG price dynamics as a determining factor are needed. Thus, all factors, both supporting and hindering, need to be identified immediately so that solutions can be found in efforts to optimize Indonesian coal exports to Japan.